2000
DOI: 10.1590/s0100-879x2000000200012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of emotional reactivity on inhibitory avoidance in the elevated T-maze

Abstract: The possibility of the presence of inter-individual emotional differences and the memory performance of rats was examined in the elevated T-maze. Two kinds of aversively motivated behaviors, inhibitory avoidance and escape learning, were measured. Based on the number of trials to achieve a learning criterion, rats were divided into two subgroups with either low or high avoidance reactivity (LAR or HAR, respectively). Retention test avoidance latencies showed that HAR animals had better avoidance memory (Mann-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…As for the "Before I was sad, now I feel happy"-theme, the analyses showed that all participants reported to have different feelings during the act of emotional recollection than during the recall of a mundane fact. This is line with what should be expected from studies of both animal (Conde, Costa and Tomaz, 2000) and human psychology (e.g.…”
Section: Empirical Findings and Analysissupporting
confidence: 92%
“…As for the "Before I was sad, now I feel happy"-theme, the analyses showed that all participants reported to have different feelings during the act of emotional recollection than during the recall of a mundane fact. This is line with what should be expected from studies of both animal (Conde, Costa and Tomaz, 2000) and human psychology (e.g.…”
Section: Empirical Findings and Analysissupporting
confidence: 92%
“…Repeatedly placing the rat inside the enclosed arm to explore the maze allows the animal to learn not to enter open arms (inhibitory avoidance learning). Re-exposing the animal to the situation after a time interval assesses memory of emotional related behavior, whereas placing the animal in an open arm produces unlearned escape responses into the enclosed arms (Conde et al, 2000).…”
Section: Behavioral Testsmentioning
confidence: 99%
“…Placing them at the end of one open arm produces an escape response generally to the enclosed arm (Zangrossi and Graeff, 1997). Re-exposing the animals to the same situation after a time interval assesses memory of these emotionally related behaviors (Conde et al, 2000). Conde and colleagues (2000) demonstrated that a multi-trial training-to-criterion (criterion of 5 minutes not evading to the open arms) increased avoidance and escape performance on later trials.…”
Section: Behavioral Testsmentioning
confidence: 99%